Fertility and savings contractions in China: long-run global implications - Zhou, Yixiao; Tyers, R.; Golley, J. (Wiley-Blackwell Publishing, 2017)
Following three decades of rapid but unbalanced economic growth, China's reform agendas are set to rebalance the economy towards consumption while maintaining strong GDP growth. Headwinds include a demographic contraction that will bring negative labour force growth and rapid ageing. Rising aged dependency combined with lower saving rates will rebalance the economy, but they will reduce both GDP growth and real per capita income. While an effective two‐child policy could sustain growth and eventually mitigate the aged dependency problem, it would set real per capita income on a still lower path. These conundrums are examined using a global economic and demographic model, which shows how the continuing demographic and saving contractions in China would alter the trajectories of both the Chinese and global economies.